1999
DOI: 10.1093/clinchem/45.8.1190
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanism for in Vitro Complement Activation in Blood and Plasma Samples: Futhan/EDTA Controls in Vitro Complement Activation

Abstract: Background: Ongoing in vitro complement (C) activation in citrate or EDTA plasma has prevented an accurate analysis of C-activation products generated in vivo. The aim of this study was to characterize handling and storage conditions required to prevent in vitro C activation in blood and plasma samples collected with Futhan/EDTA. Methods: BiotrakTM RIAs were used to quantitatively measure C3a and C4a in blood and/or plasma samples from healthy individuals (controls) and from liver transplant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…This may introduce error to in vitro measurements of in vivo-generated cleavage products, such as C3a or C5a. Addition of FUT-175 to plasma samples at the time of sample collection provides additional protection from ex-vivo activation and, therefore, ensures more accurate measurements reflecting the circulating levels of complement activation [23].…”
Section: Methodsmentioning
confidence: 99%
“…This may introduce error to in vitro measurements of in vivo-generated cleavage products, such as C3a or C5a. Addition of FUT-175 to plasma samples at the time of sample collection provides additional protection from ex-vivo activation and, therefore, ensures more accurate measurements reflecting the circulating levels of complement activation [23].…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, even when thawed at this temperature, plasma collected with EDTA remained stable for up to 60 minutes, except for measures of C4d . Other investigators have shown that cleavage of complement proteins occurs in vitro despite the use of EDTA in blood collection . Careful and systematic sample processing to avoid in vitro complement activation is therefore required for more accurate measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Careful and systematic sample processing to avoid in vitro complement activation is therefore required for more accurate measurement. Futhan, a broad‐specificity protease inhibitor, blocks in vitro complement activation . It has been shown to inhibit the esterolytic activities of C1r, C1s, and factor B and hemolytic activities mediated by both the classical and alternative complement pathways .…”
Section: Introductionmentioning
confidence: 99%
“…C3 is an inherently unstable protein that converts to C3b by spontaneous hydrolysis of the thioester bond (Pangburn et al 1981). Furthermore, complement activation may occur in vitro even in the presence of protease inhibitors generating further cleavage products from C3b, including iC3b, C3c and C3d (Pfeifer et al 1999;Momeni et al 2012). Following hydrolysis to form C3b and subsequent cleavage to yield the inhibited form iC3b, C3 undergoes major conformational changes including progressive unfolding, although the precise nature of these changes is debated (Janssen et al 2007;Ajees et al 2007).…”
Section: Discussionmentioning
confidence: 99%